Titanium - Lütjering, Gerd; Williams, James C. (Springer Berlin Heidelberg, 2003)
This comprehensive summary of the current state of the art of titanium addresses, in varying levels of detail, all aspects of titanium, including: basic characteristics and physical metallurgy, the extractive metallurgy, the various production processes, the correlations between processing, microstructure and properties, and all aspects of applications including economic ones. The book covers commercial pure (CP) titanium, alpha + beta and beta alloys, as well as titanium based intermetallics and titanium matrix composites. Richly illustrated with more than 300 figures, this compendium takes a conceptual approach to the physical metallurgy and applications of titanium, making it suitable as a reference and tutorial for materials scientists and engineers
Keywords: Materials Science; Metallic Materials; Materials science; Metals; Titanlegierung; Metallurgie; Metallischer Werkstoff; Titan